“An Unusual Pattern of Metastasis” Metastatic Malignant Thymoma Presented with Breast Lump: A Case Report and Literature Review - Kah-Seng Khoo; Kavinya Diana T. Nadesalingam; Diana Bee-Lan Ong; Li-Ying Teoh; Mei-Sze Teh; Suniza Jamaris; Mee-Hoong See (Case Reports in Surgery)
Metastatic lesions to the breast from extramammary malignant neoplasms are rare and reported account for 0.5–6.6% of all breast malignancies. Distant metastasis of thymoma is even rarer, especially to extrathoracic regions. We reported a woman with invasive malignant thymoma postneoadjuvant and resection of the thymoma, who developed breast metastasis 7 years later. Breast imaging showed high-density lesion with no intralesional microcalcifications and no significant axillary lymphadenopathy. Core biopsy and histopathology proved the lesion to be metastatic thymic carcinoma. Despite rarity, breast lumps with underlying extramammary malignancy should raise the suspicious of breast metastasis.